Strategy for Financial Well-being among public servants in Malaysia - Wahab, Nurul Najwa; Yaacob, Zulnaidi (Journal of Techno-Social, 2018)
This study investigated the determinant factors of financial well-being among public servants in Malaysia. To achieve the said objective, three independent variables that are widely discussed in the literature were tested, namely, financial literacy, financial management, and attitude toward savings. In completing the study, 139 questionnaires were completed by respondents using simple random sampling. Based on regression analysis, this study found that all three determinant factors under study have significant relationships with financial well-being. The findings of this study are supported by most of previous studies. This study has successfully filled in the literature gap by presenting evidence of determinant factors of financial well-being among public servants of an emerging economy that is still not well addressed in the literature. The implications of this study have also been discussed.